Experimental and Numerical Study of Ground-Source Heat Pumps - Christou, Christakis (My University, 2026)
Ground Source Heat Pump (GSHP) systems have emerged as a highly efficient and environmentally sustainable technology for heating and cooling applications in residential, commercial, and public buildings. Their growing adoption is driven by their capacity to significantly reduce energy consumption and greenhouse gas emissions while utilizing shallow geothermal energy as a renewable resource. Nevertheless, challenges associated with high initial investment costs, system optimization, and climatic adaptation continue to limit their wider implementation, particularly in Mediterranean regions. This thesis investigates the performance, design, cost-effectiveness, and dynamic behavior of GSHP systems operating under Mediterranean climatic conditions, with a particular focus on Cyprus. The research combines an extensive literature review with experimental investigation, economic evaluation, and advanced dynamic simulation of a large-scale geothermal installation located in the historic Municipal Library of Limassol, Cyprus. The study examines multiple ground heat exchanger (GHE) configurations integrated into a single GSHP system, including vertical borehole heat exchangers, double helicoidal coils installed in wells, and open-loop groundwater systems. Continuous operational monitoring through a Building Management System (BMS) enabled the collection of high-resolution data related to thermal loads, flow rates, inlet and outlet temperatures, energy transfer, and heat pump performance in both heating and cooling modes. The experimental analysis demonstrates that GSHP systems operating in Mediterranean climates can achieve high seasonal efficiencies, with seasonal coefficients of performance (SCOP) ranging between 4.5 and 5.0. Results further indicate that open-loop groundwater heat exchangers provide the highest thermal exchange rates and the lowest installation cost per unit of delivered energy when groundwater availability permits. Comparative economic analysis revealed significant differences in cost-effectiveness among the investigated GHE configurations, highlighting the importance of site-specific geological and hydrogeological conditions in system selection and design. To further investigate system behavior, a physics-based dynamic simulation model was developed in the Modelica environment using the Buildings library and validated against measured operational data. The model successfully reproduced both transient and steady-state thermal responses of the GSHP system, including borehole heat exchange processes, heat pump operation, and building thermal interactions. Good agreement between measured and simulated results confirmed the reliability of Modelica-based approaches for predicting GSHP performance under real operating conditions. Overall, this thesis contributes to the understanding of geothermal heat pump technologies in Mediterranean environments by integrating technical, economic, and simulation-based analyses into a unified framework. The findings demonstrate that properly designed and optimized GSHP systems can provide substantial energy savings, reduced environmental impact, and long-term economic benefits. Furthermore, the work offers practical guidance for the design, operation, and optimization of geothermal systems in historic and modern buildings, supporting the broader deployment of renewable energy technologies in the built environment.
Keywords: Ground Source Heat Pump (GSHP)